(3GdSge GdUGFH aj bVGA Ojf GdZGFHs - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s
(3ChdgG (B:s
(3CeG HYO abO SFd Yf TNU Qgf YjfG HOjf hMd hZGH ef dg GdOjf aGMVQ GdQGgf GdeOjhf GdOjf s
(3BNQgG (B:s
(3hGdMeO ddg hMOgq s
(3Vef eLehY , JQJjHgG (B: 4s
(3HgG fXGe GdJYbjHIs
(3aQZ efg eUfag SfI (B734 (3g`s
(3ai BNQg fbhd abgjI HebOGQ (B8 (3hQbGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B302s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1010s
Keywords: (3Gdabg GdTGaYjs